Quantification of the SF6 lifetime based on mesospheric loss measured in the stratospheric polar vortex. Issue 8 (19th April 2017) - Ray, Eric A.; Moore, Fred L.; Elkins, James W.; Rosenlof, Karen H.; Laube, Johannes C.; Röckmann, Thomas; Marsh, Daniel R.; Andrews, Arlyn E.
Abstract: Sulfur hexafluoride (SF6 ) is a greenhouse gas with one of the highest radiative efficiencies in the atmosphere as well as an important indicator of transport time scales in the stratosphere. The current widely used estimate of the atmospheric lifetime of SF6 is 3200 years. In this study we use in situ measurements in the 2000 Arctic polar vortex that sampled air with up to 50% SF6 loss to calculate an SF6 lifetime. Comparison of these measurements with output from the Whole Atmosphere Community Climate Model (WACCM) shows that WACCM transport into the vortex is accurate and that an important SF6 loss mechanism, believed to be electron attachment, is missing in the model. Based on the measurements and estimates of the size of the vortex, we calculate an SF6 lifetime of 850 years with an uncertainty range of 580–1400 years. The amount of SF6 loss is shown to be consistent with that of HFC‐227ea, which has a lifetime of 670–780 years, adding independent support to our new SF6 lifetime estimate. Based on the revised lifetime the global warming potential of SF6 will decrease only slightly for short time horizons (<100 years) but will decrease substantially for time horizons longer than 2000 years. Also, the use of SF6 measurements as an indicator of transport time scales in the stratosphere clearly must account for potential influence from polar vortex air. Key Points: Atmospheric lifetime of SF6 reduced by nearly a factor of 3 based on measurements in the stratospheric polar vortex Consistency of SF6 and HFC‐227ea derived mean age of air gives independent confirmation of SF6 lifetime reduction The signal of mesospheric loss or production of a trace gas is highly concentrated in the stratospheric polar vortices each winter Plain Language Summary: We have calculated an atmospheric lifetime of the molecule SF6 based on trace gas measurements in the stratospheric polar vortex. This lifetime is 3 times shorter than the commonly used lifetime over the past 20 years. Since SF6 is a greenhouse gas this adjustment has implications for long‐term climate effects.